Challenges in simultaneous validation of mental health screening tools in multiple languages: Adolescent assessments in Hausa and Pidgin in Nigeria - Bonnie N. Kaiser; Cynthia Ticao; Chukwuemeka Anoje; Jeremy Boglosa; Temitope Gafaar; John Minto; Brandon A. Kohrt (Elsevier, 2022)
Background: With growing global recognition of the need to address mental health, a key challenge is determining who needs mental health services. Most self-report screening tools were developed in English-speaking high-income settings, and this cultural milieu influences the types and content of items, the manner in which items are asked, and the options for responding to items. Approaches have been developed for transcultural translation and validation. However, these approaches are typically applied in one language at a time, which is of limited utility in linguistically diverse settings. Methods: To address challenges in cross-cultural validation, we undertook a unique process of simultaneously validating tools in two languages in Nigeria. Through this dual-language validation, we explored how cultural and contextual differences may influence what is considered valid for a mental health tool. We validated the Depression Self Rating Scale, Child PTSD Symptom Scale (CPSS), and Disruptive Behavior Disorders Rating Scale with a community sample of 330 adolescents aged 12-17. Validity was assessed in Hausa and Pidgin, two languages commonly spoken in Nigeria. Clinical psychologists used the Kiddie-Schedule for Affective Disorders and Schizophrenia to establish caseness. Results: Most items had good discriminant validity, except on the CPSS, on which only 8 of 17 items discriminated by caseness. Findings indicate the influence of culture (e.g., linguistic differences in translatability of items) and context (e.g., items that reflect experiences of hunger or foodborne illness; different PTSD caseness by language might reflect differential trauma exposure between populations). We also identified items that operated differently between languages. Conclusion: We identified shortcomings in cross-cultural validation procedures with regard to determining whether language, context, or or other differences influence performance of items. For future validation efforts, we recommend systematically collecting information on context and stressful/traumatic exposures as a way to contextualize interpretation of the validity findings. Acronyms: Depression Self Rating Scale (DSRS), Child PTSD Symptom Scale (CPSS), Disruptive Behavior Disorders Rating Scale (DBDRS), Oppositional Defiant Disorder (ODD), Conduct Disorder (CD), Area Under the Curve (AUC), Diagnostic Odds Ratio (DOR), Low- and Middle-Income Countries (LMICs), Posttraumatic Stress Disorder (PTSD).